Open-Access-Publikationsworkflow für akademische Bücher - Böhm, David (HTWK Leipzig - OA-Hochschulverlag, 2020)
"The need for an immediate, transparent and sustainable dissemination of current research has become a prerequisite for the further development of science today. Making research results freely available online as Open Access is considered to achieve the widest possible dissemination worldwide. Everyone can access anywhere Open Access publications without any restrictions or paywalls. Meanwhile more and more academic institutions and universities have already started their own presses to publish books Open Access. In the present manual a sustainable and ideal workflow for producing and publishing academic books is presented. That workflow enables universities to publish their publications both as Open Access and printed books in a state-of-theart way and without any restrictions regarding the license, the variety of formats, print run etc. As proof of concepts we have processed different use cases which demonstrates the current status of the technically and economically possibilities in the publishing sector. Furthermore, data on time, costs and personnel resources were determined, which can be used by other universities and academic institutions to indicate the necessary investments for founding and operation of their own Open Access university presses."